Interest in insect die-off and intention for action using Google trends - Felgentreff, Esther; Buchholz, Sascha; Straka, Tanja (Dryad, 2022)
1. The publication of “More than 75 percent decline over 27 years in total
flying insect biomass in protected areas” by Hallmann et al. in October
2017 gained vast media coverage in Germany. The insect crisis as
conservation topic has received little attention among the public before,
but since media influences people’s awareness, we investigated i) whether
the study publication induced increased awareness among the German public
for insect die-off, and ii) whether it contributed to people’s intentions
to undertake insect protecting actions. 2. We used Google Trends to
examine the people’s internet activity in terms of keywords relevant to
our research question. 3. A high peak in Google searches for insect
die-off (Insektensterben) was indeed visible just after the study
publication, and search volume remained significantly higher for the
following six months, confirming that the topic gained attention. 4.
Searches for the three keywords insect hotel, bee friendly and bee meadow
increased significantly over the summers of the years 2017 to 2019. This
suggests that intentions to undertake these simple insect protecting
actions rose as well. The results propose that media should use the window
of opportunity opened by shocking news about a crisis to spread
information on feasible counteractions. 5. Due to the prevailing
topicality in the media and the already increased awareness and
willingness to action among the population, conservation organizations can
take advantage of the situation by communicating practical conservation
measures to the general public in cooperation with media agencies or via
own channels such as press releases and social media campaigns.
The data was downloaded from Google Trends. It was searched for the index
of search activity for the four German keywords
"Insektensterben" ("insect die-off"),
"Insektenhotel" ("insect hotel"),
"bienenfreundlich" ("bee friendly") and
"Bienenweide" ("bee meadow"). For all four keywords,
query data was used rather than query collections, which is an additional
feature of Google trends that includes related searches. The geographical
range was restricted to Germany, and data was downloaded for the time span
between January 3, 2016, and December 22, 2019. It was then analyzed with
R, where the data sets were divided into different sections and compared
with each other.
Keywords: Google trends; Conservation culturomics; Cultural entomology; Public perception; Insect die-off; Biodiversity crisis; FOS: Biological sciences